Effect of Cosolutes on the Sorption of Phenanthrene onto Mineral Surface of River Sediments and Kaolinite - Wu, Yinghong (Hindawi Publishing Corporation, 2014)
Sorption of phenanthrene onto the natural sediment with low organic carbon content (OC%), organic-free sediment, and kaolinite was investigated through isotherm experiments. Effects of cosolutes (pyrene, 4-n-nonyphenol (NP), and humic acid (HA)) on phenanthrene sorption were also studied by comparing apparent solid-water distribution coefficients (K (d) (app)) of phenanthrene. Two addition sequences, including “cosolute added prior to phenanthrene” and “cosolute and phenanthrene added simultaneously,” were adopted. The Freundlich model fits phenanthrene sorption on all 3 sorbents well. The sorption coefficients on these sorbents were similar, suggesting that mineral surface plays an important role in the sorption of hydrophobic organic contaminants on low OC% sediments. Cosolutes could affect phenanthrene sorption on the sorbents, which depended on their properties, concentrations, and addition sequences. Pyrene inhibited phenanthrene sorption. Sorbed NP inhibited phenanthrene sorption at low levels and promoted sorption at high levels. Similar to NP, effect of HA on phenanthrene sorption onto the natural sediment depended on its concentrations, whereas, for the organic-free sediment and kaolinite, preloading of HA at high levels led to an enhancement in phenanthrene K (d) (app) while no obvious effect was observed at low HA levels; dissolved HA could inhibit phenanthrene sorption on the two sorbents.